Bazaars and Video Games in India. (December 2016) - Deka, Maitrayee
This article examines the history of video games in India through the lens of Delhi's electronic bazaars. As many gamers shifted from playing Atari Games in the 1980s to PlayStation in the 2000s, we see a change in the role that the bazaars play. Throughout the 1980s and 1990s, the bazaars were the crucial channels of smuggling video games into India. In the 2000s, the bazaars face competition from official channels. Increasingly, the branded showrooms and online market attract elite consumers who can afford to buy the latest original video game. I argue that, while in the twenty-first century, the electronic bazaars have seen a decline in their former clientele, they now play a new role: they have become open places through the circulation of "obsolete" video games, and the presence of a certain bazaari disposition of the traders. The obsolete games in the form of cartridge, cracked console, and second hand games connect video games to people outside the elite network of corporate and professional new middle class. This alongside the practice of bargaining for settling price creates dense social relationships between a trader and a consumer.